2012
DOI: 10.1111/j.1751-7176.2011.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet Therapy for Transient Ischemic Attack

Abstract: J Clin Hypertens (Greenwich).****;**:**–**. ©2011 Wiley Periodicals, Inc. Transient ischemic attack (TIA) is currently defined as a transient episode of neurologic dysfunction caused by focal brain, spinal cord, or retinal ischemia without infarction. TIA is an important risk factor for stroke and other major vascular events. Risk factors for TIA or stroke need to be addressed effectively to reduce the risk for stroke in patients who have had a TIA. Aspirin (ASA) significantly reduces the risk for stroke when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The results are comparable with an American study that reported use of warfarin by 42% of patients with AF at high risk of stroke, and by 44% of patients with moderate stroke risk. 12 Aspirin significantly reduces the risk of stroke in patients who experienced a transient ischaemic attack (TIA) or stroke, 13 and should be given as soon as possible after onset and continued as long-term antiplatelet therapy. 14 Our analysis showed that an increasing number of patients were receiving aspirin as a monotherapy after a TIA or ischaemic stroke event, reaching around one-quarter of the at-risk group in March 2010.…”
Section: Discussionmentioning
confidence: 99%
“…The results are comparable with an American study that reported use of warfarin by 42% of patients with AF at high risk of stroke, and by 44% of patients with moderate stroke risk. 12 Aspirin significantly reduces the risk of stroke in patients who experienced a transient ischaemic attack (TIA) or stroke, 13 and should be given as soon as possible after onset and continued as long-term antiplatelet therapy. 14 Our analysis showed that an increasing number of patients were receiving aspirin as a monotherapy after a TIA or ischaemic stroke event, reaching around one-quarter of the at-risk group in March 2010.…”
Section: Discussionmentioning
confidence: 99%